2014
DOI: 10.1016/j.intmar.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Consumer–Brand Relationships in Social Media Environments: The Role of Parasocial Interaction

Abstract: As brands solidify their place in social media environments, consumers’ expectations have amplified, thus spurring the development of technologies to assist with the engagement process. Understanding the ways in which brands can preserve the one-to-one characteristics and intimate relationship qualities offered by social media while still meeting consumer expectations amidst the escalating volume of interactions has become essential. Drawing on the communications literature, this research proposes that parasoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
519
2
24

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 633 publications
(566 citation statements)
references
References 58 publications
21
519
2
24
Order By: Relevance
“…Several other studies have shown that the interactivity that brings about the perception of a conversational human voice is an important driver of positive effects of exposure to brands in social media (e.g., van Noort & Willemsen, 2011;Park & Lee, 2013;Sweetser & Metzgar, 2007;Yang, Kang, & Johnson, 2010). Some authors (Colliander & Dahlen, 2011;Labrecque, 2014) have found similar effects but refer to theories on parasocial interaction to explain the effects. The concept of parasocial interaction has previously been developed to explain the relationship people experience with TV characters, which in some ways resembles the relationships people experience with real people (Horton & Wohl, 1956).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have shown that the interactivity that brings about the perception of a conversational human voice is an important driver of positive effects of exposure to brands in social media (e.g., van Noort & Willemsen, 2011;Park & Lee, 2013;Sweetser & Metzgar, 2007;Yang, Kang, & Johnson, 2010). Some authors (Colliander & Dahlen, 2011;Labrecque, 2014) have found similar effects but refer to theories on parasocial interaction to explain the effects. The concept of parasocial interaction has previously been developed to explain the relationship people experience with TV characters, which in some ways resembles the relationships people experience with real people (Horton & Wohl, 1956).…”
Section: Discussionmentioning
confidence: 99%
“…Parasocial interactions arise when individuals are repeatedly exposed to a media persona, resulting in the individuals developing a sense of intimacy, perceived friendship, and identification with the celebrity (Horton and Wohl 1956). Labrecque (2014) proposes that parasocial interactions may be used as a theoretical lens for designing successful social media strategies for a brand. She finds that this sense of feeling connected with the brand goes beyond the interaction itself and drives increased feelings of loyalty intentions as well as willingness to provide information to the brand.…”
Section: Social Media and Parasocial Interactionsmentioning
confidence: 99%
“…Simultaneously, it is pointed out that it is important for the relationships between the brand and the customer (social media user) to be of personal nature or for the client to have such an impression. It translates into the effect of customer loyalty towards the brand as well as tendency to provide it with information (Labrecque, 2014). Social media may therefore also serve as an area of study on the brand itself (Beuker, Abbing, 2010).…”
Section: Brand Sponsorship Of Events In the Light Of Social Media Conmentioning
confidence: 99%